Current Practice of Hepatocellular Carcinoma Surveillance - Imelda Maria Loho; Lianda Siregar; Agus Sudiro Waspodo; Irsan Hasan (Interna Publishing, 2019)
Hepatocellular carcinoma (HCC) is the second most common cause of cancer-related death worldwide. This is due to the heterogeneity of the tumor biology and lack of curative treatment options. The most significant prognostic factor is detection at early stage and thus, surveillance strategies are of high importance. High-risk patients should undergo ultrasound and tumor marker tests at six-month interval in order to detect HCC at the earlier stage. However, in real-life practice, ultrasound has several limitations and the adherence to HCC surveillance is suboptimal due to various provider, patient, and health-care system factors. In this paper, we will address current methods of HCC surveillance and obstacles found in real-life practice.